MENGINTEGRASIKAN MANAJEMEN SUMBER DAYA MANUSIA DI MADRASAH - Wahyudin Noor (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2017)
Human resource management is part of organizational management that is supposed to focus on human resources. Observing the importance of the role of human resources in the organization of this madrasah, at least is to reconciling the development of the work environment that occurs-especially in the world of Islamic education today, so that madrasah should be able to pay attention to the importance of human resource management programs through the practice of integrating human resources management including human resource planning, recruitment, selection, orientation and placement, training and development, job assessment and compensation into planning, management and control of madrasah organizations related to allocation and human resource development in madrasah Keywords. Management, Human Resource Development, Madrasah.